Evaluation of real-world follow-up methods and their association with adherence and safety in adjuvant breast cancer therapy: a retrospective study - Li, Na; Zhang, Qian; Yang, Xiaomei; Li, Xiaoli; Tian, Xixi; Li, Wei; Ren, Lili; Yang, Hua (Frontiers in Oncology, 2025)
AimTo compare the associations between different follow-up management methods—telephone, WeChat, and mini-program—and treatment compliance, safety, quality of life, and self-management in breast cancer patients receiving adjuvant therapy.MethodsThis retrospective study reviewed clinical and follow-up records of patients with newly diagnosed breast cancer who underwent adjuvant therapy after radical surgery. Based on documented follow-up modes, patients were categorized into three groups: telephone, WeChat, and the “Doctor Haixin” mini-program. Key clinical indicators, including treatment adherence, quality of life, adverse events, and self-management levels, were extracted from medical records and patient-reported follow-up data collected over a 12-week period.ResultsPatients in the mini-program group were found to have higher recorded adherence rates and better self-reported outcomes in quality of life and self-management compared with the telephone and WeChat groups. All groups showed improved quality of life over time, while adverse event rates remained comparable across groups.ConclusionAmong patients retrospectively assessed, those managed via the mini-program follow-up exhibited more favorable patterns in adherence and patient-reported outcomes. These findings suggest that digital platforms may be associated with enhanced care quality in the context of breast cancer follow-up.